KAJIAN KEMAMPUAN SISWA DALAM PEMBELAJARAN KIMIA DITINJAU DARI LITERASI SAINS PISA KELAS XII SMAN 1 TELUK KERAMAT - Tomi Tomi; Dini Hadiarti; Rody Putra Sartika (Universitas Muhammadiyah Pontianak, 2016)
ABSTRACT Science literacy is a key to face the challenge in this global era. It becomes a demand to be mastered by every individual whether in daily life or work field. An individual who is aware of science can use the scientific information that he has, to solve the problem in daily life. This research is done to give a description about twelve grade students' ability in learning chemistry based on PISA science literacy in SMAN 1 Teluk Keramat. The method applied in this research is quantitative descriptive. The sample of this research were twelve grade students of SMAN 1 Teluk Keramat. To collect data, the writer implemented some techniques. Those are measurement technique and direct communication technique. The instruments in collecting data in this research are students' achievement test in the form of essay and multiple choice in a passage. Based on the research findings, it showed that chemistry learning in SMAN 1 Teluk Keramat have already trained students' ability in science literacy. It is found that the students' ability in science literacy is about 68,91% for the content science ability which is categorized as intermediate level and 68,91 for the context science ability, categorized as intermediate level. Keywords: Students' ability, science literacy, chemistry learning